SPEED OF CHANGE OF RNK AND DNK CONTENTS IN A BONE MARROW OF THE RADIATION-EXPOSED ANIMALS - Петрина, Л. Г. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Experimental researches were conducted on male rats of Vistar line with the initial mass of body 150-180 grams. Single irradiation of animals were conducted in doses of 0,2; 0,5; 1,0; 3,0; 5,0; 7,0 and 9,0 Gy with powers of a dose 0,1 Gy/min. The contents of nucleinic acids in a bone marrow was detected in 0, 5, 1, 2, 4, 6, 8, 10, 15, 20, 30, 45, 60, 90, 120 days after the influence. Control tests were conducted simultaneously with each series of investigation conducted on animals of corresponding age. Results of the experiments that the RNA and DNA contents in the bone marrow of animals are change wavily under the influence of irradiation depending on the functional condition of an organism and development of the pathological process. The speed of change RNA and DNA contents in a rats bone marrow and amplitude of oscillations of change of DNA, RNA contents, RNA/DNA ratio depended on the dose received by animals and changed in wavily in all animals groups. Growth of change of RNA/DNA ratio in a bone marrow can indicate the increase of amount of young cells in it; decrease indicates lowered albumens synthesizing ability of system.